The Sarchasm: Sarcasm Production and Identification in Spontaneous Conversation. Issue 5 (2nd July 2020) - Fox Tree, Jean E.; D'Arcey, J. Trevor; Hammond, Alicia A.; Larson, Alina S.
ABSTRACT: We tested sarcasm production and identification across original communicators in a spontaneously produced conversational setting, including testing the role of synchronous movement on sarcasm production and identification. Before communicating, stranger dyads participated in either a synchronous or nonsynchronous movement task. They then completed a task designed to elicit sarcasm, although no instruction to produce sarcastic content was provided. After communicating, participants immediately reviewed their conversations and identified their own and their addressees' sarcastic utterances. No definition of sarcasm was provided. We found that participants who had moved synchronously identified more sarcasm in their own productions. They did not identify more sarcasm in their partner's productions however. We also discovered that most identifications of sarcasm did not align across conversational participants, and neither did those of outside observers. People reported sarcasm in their addressees commensurate with the sarcasm they produced, rather than the sarcasm that their addressees self-reported. There were numerous cases of sarchasm, where producers' intended sarcasm was not identified by addressees.